K0 test and particle flow simulation of coral sands with different gradations - Zhang, Ruiyuan; Zhang, Yongtao; Chen, Peishuai; Ji, Fuquan; Luo, Huiwu; Zhong, Yu (Frontiers in Earth Science, 2025)
This paper performs a series of laboratory static lateral pressure coefficient (K0) tests on coral sands with five typical gradations in dry and saturated states via water bladder type lateral pressure apparatus to investigate their ranges of K0 values. The results reveal that the K0 values of coral sands in dry and saturated states range from 0.22 to 0.32 and 0.27 to 0.33, respectively, and that there is an exponential function relationship between the particle gradation and the K0. On this basis, a discrete element model is established with the aid of particle flow code (PFC), and the numerical simulation and laboratory test are in good agreement. The displacement field of coral sand with a narrower gradation is revealed to be more prone to exhibit a horizontally stratified compression feature at the meso-scale. The coral sand with a wider gradation exhibits a more obvious gradient distribution of internal contact forces with more uniform directional distribution and better compaction. The K0 decreases and then stabilizes with increasing particle bonding strength, and the evolution law between them conforms to the exponential function form. A theoretical calculation formula of K0 for coral sand based on the distribution coefficient is further proposed according to the laboratory test results. The research results of this paper can provide parameter support for construction and design of wharf retaining structures on islands and reefs.